2018
DOI: 10.1002/rra.3376
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the effect of environmental flow duration on seedling emergence from riparian seed banks of the Upper Hunter River, New South Wales

Abstract: Passive riparian revegetation techniques are important tools in river rehabilitation.However, the utility of the sediment seed bank as a passive riparian regeneration option is poorly understood. After modelling a range of flows for field-surveyed cross sections, a glasshouse seedling emergence experiment was undertaken to compare the effects of simulated flow duration on seedling emergence of desirable riparian species that occur on benches of the gravel-bedded Hunter River near Muswellbrook, New South Wales.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Moving laterally from the river channel to the riparian zone, the study of Stone, Fryirs, and Leishman (2020) shows how passive riparian revegetation techniques are important tools in river rehabilitation. Results from emergence experiments show the duration of inundation to influence seed germination for most riparian vegetation species, but variations between species complicate successful recruitment.…”
Section: Examples Of Riverine Landscapes Water Resource Developmentmentioning
confidence: 99%
“…Moving laterally from the river channel to the riparian zone, the study of Stone, Fryirs, and Leishman (2020) shows how passive riparian revegetation techniques are important tools in river rehabilitation. Results from emergence experiments show the duration of inundation to influence seed germination for most riparian vegetation species, but variations between species complicate successful recruitment.…”
Section: Examples Of Riverine Landscapes Water Resource Developmentmentioning
confidence: 99%
“…Germination rates for A. stenophylla without pods were higher in the I40 treatment than in the I20 treatment, showing that extended flooding improves germination rates. Inundation has also been found to improve germination rates of other riverine Acacia species such as Acacia salicina and Acacia parvipinnula (Stone et al 2020). Two germinants from seeds without pods were present while fully submerged in the water in the I40 treatment from Day 31, and the number of germinants increased following recession, demonstrating that A. stenophylla seeds are able to germinate under water to a depth of 50 mm and after flood events.…”
Section: Discussionmentioning
confidence: 89%
“…A study linking hydro period with vegetation response showed that wetland species richness and density was related to flood frequency (Battaglia and Collins, 2006;Shoemaker and Ervin, 2019). Other studies found no relationship between flood frequency, species richness and density in soil seed banks (Capon and Brock, 2006;Webb et al, 2006;Stone et al, 2018;Baskin, Baskin and Chester, 2019) or fewer species in low flood frequency zones (Capon, 2007). Other than flooding, human disturbances such as cultivation in wetlands have increased around the world (McCartney et al, 2010;Rebelo et al, 2010;Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%